2021
DOI: 10.3389/fcell.2020.622308
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Palatal Dentition of Axolotl Arises From a Common Tooth-Competent Zone Along the Ecto-Endodermal Boundary

Abstract: Vertebrate dentitions arise at various places within the oropharyngeal cavity including the jaws, the palate, or the pharynx. These dentitions develop in a highly organized way, where new tooth germs are progressively added adjacent to the initiator center, the first tooth. At the same time, the places where dentitions develop house the contact zones between the outer ectoderm and the inner endoderm, and this colocalization has instigated various suggestions on the roles of germ layers for tooth initiation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…To describe the earliest events and the sequence of appearance of tooth fields during the sterlet odontogenesis, we followed the expression of Pitx2 and Shh , two genes generally expressed in the future dental epithelium and responsible for the differentiation of the oral epithelium toward a dental fate 28‐33 . Recently, we showed that, in the Mexican axolotl, Pitx2 is expressed in broader regions prefiguring the positions of tooth fields while Shh is expressed focally in tooth germs 34 . Concordantly, Pitx2 in the sterlet is expressed broadly at positions of future tooth fields and only later (at around 12‐14 mm TL) becomes expressed focally in the developing tooth germs (Figure 3A‐J, arrows and arrowheads).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To describe the earliest events and the sequence of appearance of tooth fields during the sterlet odontogenesis, we followed the expression of Pitx2 and Shh , two genes generally expressed in the future dental epithelium and responsible for the differentiation of the oral epithelium toward a dental fate 28‐33 . Recently, we showed that, in the Mexican axolotl, Pitx2 is expressed in broader regions prefiguring the positions of tooth fields while Shh is expressed focally in tooth germs 34 . Concordantly, Pitx2 in the sterlet is expressed broadly at positions of future tooth fields and only later (at around 12‐14 mm TL) becomes expressed focally in the developing tooth germs (Figure 3A‐J, arrows and arrowheads).…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30][31][32][33] Recently, we showed that, in the Mexican axolotl, Pitx2 is expressed in broader regions prefiguring the positions of tooth fields while Shh is expressed focally in tooth germs. 34 Concordantly, Pitx2 in the sterlet is expressed broadly at positions of future tooth fields and only later (at around 12-14 mm TL) becomes expressed focally in the developing tooth germs (Figure 3A-J, arrows and arrowheads). On the other hand, Shh is expressed focally already when Pitx2 shows broad field-specific expression pattern (Figures 2H and 3K-M, P-R).…”
Section: Expression Of Early Odontogenic Genes Marks Positions Of Too...mentioning
confidence: 92%
“…Odontogenesis is poorly understood in amphibians, especially when compared to our understanding of tooth development in fishes and amniotes (Fraser et al 2004;Tucker and Sharpe 2004;Thiery et al 2017). It is not yet known if all the genes critical for tooth formation in fishes and amniotes are also expressed during the morphogenesis of teeth in amphibians (but see Soukup et al 2021). Investigating the developmental genetics of tooth formation in the jaws of frogs may provide insights into whether a transient tooth signaling program is present in the lower jaw, providing the possible mechanism underlying the re-evolution of lost mandibular teeth in G. guentheri.…”
Section: Discussionmentioning
confidence: 99%
“…73 In addition, studies of axolotl dentition identified a conserved ecto-endodermal boundary as the potential mediator of tooth development across multiple species. 26 Further, loss of function studies identified that Bapx1 is necessary for jaw joint formation in multiple vertebrates, including axolotls. 74 The current body of evo-devo research using axolotl as a bridge animal have identified similarities and differences from genomic to morphological scales.…”
Section: Axolotls As Models For Evolution Of Development (Evo-devo)mentioning
confidence: 99%
“…These experiments are key to support comparative developmental studies and identify conserved and divergent regulatory modules controlling axolotl developmental and regenerative programs. So much can be done with these animals, such as gain and loss of function, 8‐10 CRISPR‐mediated transgenesis, 10,11 single‐cell characterization, 12‐16 live imaging, 17‐20 transplants and cell lineage tracing, 20‐27 and the use of ex vivo explants 28 to compare the developmental processes of this unique salamander to the robust body of avian, frog, zebrafish, and mouse developmental research. For example, axolotl gills can regenerate, yet they are one of three modes of respiration at the organism's disposal, and their full role remains unknown 29 …”
Section: Introductionmentioning
confidence: 99%